ADENINE SULFATE ON IN VITRO MULTIPLICATION OF PAPAYA TREE ‘TAINUNG 01’ - SCHMILDT, Omar; SCHMILDT, Edílson Romais; AMARAL, José Augusto Teixeira do (Scientia Agraria, 2007)
Originated papaya trees of seeds coming of open pollination they result in a genotypes mixture with considerable variation in susceptibility to diseases and in quality and income of fruits. The tissue culture appears as a viable technology for the production of seedlings with desirable agronomic characteristics. The objective of this work was it of evaluating the multiplication in papaya tree vitro 'Tainung 01' in different levels of adenine sulfate (0; 30; 60; 90 and 120 mg L-1), in modified MS multiplication medium, associate to the retreat or not of the leaves of sprouts formed in establishment medium. Nodal segments of lateral buds of juvenile plants of papaya tree were used 'Tainung 01' with 14 weeks of age. At the end of the fourth subculture, they were evaluated the fresh matter of the aerial part, the number of capable sprouts (≥ 5 mm) and no capable (< 5 mm) to the rooting, as well as the visual aspect of the tufts of sprouts. The presence of the leaves, independently of the levels of adenine sulfate, it propitiated a larger weight of the fresh matter of the aerial part and a larger number of capable sprouts to the rooting. The use of 30 mg L-1 of adenine sulfate in the middle of multiplication provided larger weights of the fresh matter and high number of sprouts, ally to a good visual aspect of the aerial part, with formation of prolonged sprouts and long petiole, presenting an appropriate pattern for the in vitro rooting of papaya tree 'Tainung 01'.